Estudo da regioquímica da ciclocondensação de enaminodicetona frente à hidrazinas : síntese de pirazóis, pirazolopiridazinonas e derivados com potencial atividade antitumoral - Silva, Michael Jackson Vieira da (2014)
The new and versatile precursor block [EtCO2C(O)C(=CHNMe2)C(O)CO2Et] (62%) for the synthesis of heterocycles was obtained from the C-acylation reaction of secondary ?-enaminoketone [EtCO2C(O)C(=CHNMe2)] with ethyl oxalyl chloride in pyridine and low temperature. The cyclocondensation reaction of such precursor with hydrazine monohydrate, phenylhydrazine and 4-chlorophenylhydrazine was regioselective leading to the heterocycles 5-carboxyethyl-4-[(oxo)acethylethoxy]-1H-pirazoles 1(R1)-substituted (R1= H, Ph, 4-ClC6H4) (67-75%) characterized using NMR techniques as regioisomers-1,5. A set of fused heterocycles 4-carboxyethyl-1H-pyrazolo[3,4-d]pyridazin-7-ones 1(R1),6(R2)-substituted (R1= Ph e 4-ClC6H4; R2= H, Ph, 4-ClC6H4) was synthetized from two reaction paths: by the reaction of 5-carboxyethyl-4-[(oxo)acethylethoxy]- 1H-pirazoles 1(R1)-substituted with hydrazine monohydrate, phenylhydrazine and 4-chlorophenylhydrazine under ethanol reflux and acid catalysis (AcOH) when R1?R2 (69-89%) and using an one-pot methodology from the precursor block ?-enaminodiketone with phenylhydrazine and 4-chlorophenylhydrazine under ethanol reflux and acid catalysis (AcOH) when R1=R2 (53-65%). The hydrazonyl pyrazoles that are intermediates in the synthesis of compounds pyrazolo[3,4-d]pyridazinones were isolated and characterized as E and Z stereoisomers which, by tests of reactivity afford the understanding of the reaction mechanism, which proceeds only through the stereoisomer E. Synthesis of N-acylhydrazine derivative (98%) and N-acylhydrazone derivative (96%) of the compound pyrazolo[3,4-d]pyridazinone was also conducted, demonstrating the synthetic potential of the precursor block ?-enaminodiketone in organic synthesis